If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 + -3n = 13 Solving 19 + -3n = 13 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + -3n = 13 + -19 Combine like terms: 19 + -19 = 0 0 + -3n = 13 + -19 -3n = 13 + -19 Combine like terms: 13 + -19 = -6 -3n = -6 Divide each side by '-3'. n = 2 Simplifying n = 2
| -37+6x=19+2x | | 3p+5q=7 | | 6+5g=3g+20 | | 4x-10=7x-9 | | 10=0.83(n+6) | | 2-(-2)s=6 | | -x-18=36 | | 0.5x+.01x+12+1x-5=9.96 | | 3d+4(-3)=11 | | 2661=63+63(n-1) | | x^2-kx+9=y | | 4x+3a=bx+2.5a-5 | | 5(x+3)-2=2x+9 | | 6x+8x-42=84-7x | | v-7.5=3.4 | | x^2+9x=15 | | 3r+1=r+8 | | 5r+7=-13+7r | | 9d+4(-7)=15 | | -7+4(1-5x)=x+39 | | y+6.4=9.66 | | X+50=76 | | 63=9(z-92) | | 7v=-10 | | 30x=-140 | | 27x+8=-170 | | -29+2x=-6x+27 | | (8*x^3-24*x^2+10)=0 | | 3+2y=x | | 5R-20=240 | | x+ky+1=0 | | x+2*4=9 |